Anticancer Effects of Lebanese Cannabis Oil Against in vivo and in vitro Models of Squamous Cell Carcinoma - Azar Atallah, Shirine (2023)
Cannabis sativa L. has a long history of use in traditional medicine for various ailments as an analgesic, anticonvulsant, hypnotic, tranquilizer, and anti-inflammatory agent. Emerging evidence in preclinical studies has also demonstrated the anticancer effect of cannabinoids, which are the major components of the plant. Recent findings established the importance of the endocannabinoid system (ECS) in the maintenance of skin homeostasis. Hence, the current study aims to investigate the potential chemotherapeutic effects of Lebanese Cannabis sativa oil extract (COE) on in vivo and in vitro squamous cell carcinoma (SCC) models, and to determine its underlying mechanism of action. GCMS analysis of COE revealed the presence of two major cannabinoids, CBD (59.1%) and THC (20.2%). Cell proliferation assay (MTS) of COE-treated tumorigenic human epidermal keratinocytes (HaCaT-ras) showed a significant dose and time dependent cytotoxicity with IC50 of 19, 11 and 8 g/mL at 24, 48 and 72 hours, respectively. Flow cytometry on COE-treated HaCaT cells demonstrated an induction of apoptotic cell death. Western blot analysis confirmed the involvement of apoptosis via both the extrinsic and intrinsic pathways and implicated an additional alteration in autophagy. Reactive oxygen species (ROS) detection assay did not show a significant involvement of oxidative stress in the cytotoxicity of COE. The anti-tumor effect of COE was also evaluated using a DMBA/TPA skin carcinogenesis mouse model. Intraperitoneal treatment of mice with COE (10, 25 or 50 mg/kg; 9 weeks) showed a non-significant decrease in tumor volume with respect to control, without adverse effects on liver and kidney function. In conclusion, COE displayed a promising anticancer activity against SCC cells, by triggering apoptosis and causing alterations in autophagy. These findings highlight the need for additional studies to investigate the role of COE in the treatment of squamous cell carcinoma.